Age reprogramming: cell rejuvenation by partial reprogramming - Singh, Prim B.; Zhakupova, Assem (Development (Cambridge), 2022)
‘Age reprogramming’ refers to the process by which the molecular and cellular pathways of a cell that are subject to age-related decline are rejuvenated without passage through an embryonic stage. This process differs from the rejuvenation observed in differentiated derivatives of induced pluripotent stem cells, which involves passage through an embryonic stage and loss of cellular identity. Accordingly, the study of age reprogramming can provide an understanding of how ageing can be reversed while retaining cellular identity and the specialised function(s) of a cell, which will be of benefit to regenerative medicine. Here, we highlight recent work that has provided a more nuanced understanding of age reprogramming and point to some open questions in the field that might be explored in the future.